Production of Vitamin B2 (Riboflavin) by Microorganisms: An Overview - Averianova, Liudmila A.; Balabanova, Larissa A.; Son, Oksana M.; Podvolotskaya, Anna B.; Tekutyeva, Liudmila A. (Frontiers in Bioengineering and Biotechnology, 2020)
This article represents an overview on microbial production of vitamin B2 (riboflavin) with detailed characterization of the riboflavin-producing microorganisms and its biosynthesis pathways known up to 2020. Riboflavin is a crucial micronutrient that is a precursor to coenzymes flavin mononucleotide (FMN) and flavin adenine dinucleotide (FAD) required for biochemical reactions in all living cells. Among for decades, one of the most applications of riboflavin that it has been used worldwide as animal and human nutritional supplement. The latest researches on riboflavin production via fermentation process is required for the development of new and improved microbial strains using biotechnology and metabolic engineering techniques to increase the yield of vitamin B2. In this paper, we describe well-known industrial microbial producers Ashbya gossypii, Bacillus subtilis, and Candida spp., and summary of its biosynthetic pathway optimization through genetic and metabolic engineering, combined with random chemical mutagenesis and rational medium components to increase riboflavin production.